2011
DOI: 10.1016/j.bone.2010.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Comparing histological, vascular and molecular responses associated with woven and lamellar bone formation induced by mechanical loading in the rat ulna

Abstract: Osteogenesis occurs by formation of woven or lamellar bone. Little is known about the molecular regulation of these two distinct processes. We stimulated periosteal bone formation at the ulnar mid-diaphysis of adult rats using a single bout of forelimb compression. We hypothesized that loading that stimulates woven bone formation induces higher over-expression of genes associated with cell proliferation, angiogenesis and osteogenesis compared to loading that stimulates lamellar bone formation. We first confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
94
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(99 citation statements)
references
References 60 publications
(85 reference statements)
5
94
0
Order By: Relevance
“…Although the precise mechanism of the present enhancement of bone regeneration is not clear, it is likely that LIPUS stimulated cellular migration, proliferation and differentiation which were controlled by these signal molecules [25,26]. It has been reported that LIPUS stimulated angiogenesis and the most effective time point of LIPUS application was at the second week when extensive angiogenesis generally occurs after the surgery [27,28]. Thus, promotion of angiogenesis by LIPUS seemed to contribute to the present enhancement of bone regeneration.…”
Section: Figurementioning
confidence: 85%
“…Although the precise mechanism of the present enhancement of bone regeneration is not clear, it is likely that LIPUS stimulated cellular migration, proliferation and differentiation which were controlled by these signal molecules [25,26]. It has been reported that LIPUS stimulated angiogenesis and the most effective time point of LIPUS application was at the second week when extensive angiogenesis generally occurs after the surgery [27,28]. Thus, promotion of angiogenesis by LIPUS seemed to contribute to the present enhancement of bone regeneration.…”
Section: Figurementioning
confidence: 85%
“…This situation differs from the exogenous mechanical stimuli implemented in the current study, which are not associated with significant hypoxia or increased angiogenesis (45), but rather, are considered anabolic. On the other hand, application of much more intensive loads that induce bone fatigue with significant tissue damage is associated with increased skeletal vascularity likely due to tissue hypoxia (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…Left limbs were used as internal controls as previously validated 21,24. The protocol for noninvasively loading the mouse tibia has been reported previously 21,25.…”
Section: Methodsmentioning
confidence: 99%